IgD/FcδR is involved in T-cell acute lymphoblastic leukemia and regulated by IgD-Fc-Ig fusion protein - Yujing Wu; Aijun Zhang; Wensheng Chen; Qianling Xin; Wenwen Pan; Xiaoxi Hu; Tao Li; Hengshi Chen; Jing Zhang; Chengxin Luan; Jian Ge; Wei Wei (Elsevier, 2023)
T-cell acute lymphoblastic leukemia (T-ALL) has a poor prognosis as a result of severe immunosuppression and rapid tumor progression with resistance to conventional chemotherapy. Excessive IgD may play a role in T cell activation via IgD Fc receptor (FcδR). Here we aimed to investigate the effects of IgD in T-ALL and demonstrated the potential benefit by targeting IgD/FcδR in T-ALL patients with IgD-Fc-Ig fusion protein. In T-ALL patients' blood samples and cell lines, the level of IgD, the percentage of FcδR expressing cells and the binding affinity were determined by flow cytometry. T cell viability, proliferation and apoptosis were analyzed. A mouse xenograft model was used to evaluate the in vivo effect of IgD-Fc-Ig, an IgD-FcδR blocker. The levels of serum IgD and FcδR were abnormally increased in part of T-ALL patients and IgD could induce over-proliferation and inhibit apoptosis of T-ALL cells in vitro. FcδR was constitutively expressed on T-ALL cells. IgD-Fc-Ig showed similar binding affinity to FcδR and selectively blocked the stimulation effect of IgD on T-ALL cells in vitro. In vivo study exhibited that IgD-Fc-Ig may also have therapeutic benefit. IgD-Fc-Ig administration inhibited human T-ALL growth and extended survival in xenograft T-ALL mice. In conclusion, this work supports the idea of targeting IgD/FcδR in T-ALL patients with excessive IgD. IgD-Fc-Ig fusion protein might be a potential biological drug with high selectivity for T-ALL treatment.